The Soundscape of "Bermulanya Di Sini…Kedah Tua"! - Pravina Manoharan; Johan Awang Othman (Wacana Seni Journal of Arts Discourse, 2019)
This article explores the relationship between soundscape, archaeological, and historical discourses within the music framework for the production of "Bermulanya Di Sini…Kedah Tua". The lack of tangible audio resources on Kedah Tua's ancient civilisation was a challenge to the initial compositional process for this production. To overcome this, the theoretical framework of soundscape ecology was employed as a working definition to understand how the different sonic vocabulary of Kedah Tua's ancient history can be reimaged and repositioned within the musical compositional structure of the play. The paper examines how the theory of soundscape ecology can be employed on the historical narratives of the past to create present day soundscape compositions that bring to life probable scenes of the daily activities and livelihood of this ancient civilisation that once flourished on a maritime trade industry between the 2nd–6th AD.